Perlindungan Hukum Pasca Perceraian: Analisis Strategi dan Implementasi di Indonesia - Noor, Tajuddin (Kajian Ilmiah Hukum dan Kenegaraan, 2025)
Purpose: This research aims to analyze post-divorce legal protection in Indonesia, focusing on its strategy and implementation, as well as to explore the challenges faced by divorced individuals in accessing their rights. Methodology/approach: The research uses the normative juridical method to analyze relevant legal norms. The researcher also examines dispute resolution mechanisms both in litigation and non-litigation. Results/findings: The results show that despite a clear legal framework, many individuals do not receive adequate legal protection. This is due to social stigma, lack of understanding of rights, and weak execution mechanisms. Conclusion: Legal protection for individuals after divorce in Indonesia still faces various challenges. It is necessary to increase the capacity of judicial institutions and public understanding to guarantee the rights of individuals after divorce. Limitations: The limitations of this research include limitations in the scope of the study which may not cover all social and cultural aspects that affect the implementation of legal protection and there may also be bias in the data used. Contribution: The contribution of this research lies in a deeper understanding of the challenges faced after divorce and provides recommendations for improvements in the legal system and protection for individuals, especially children and ex-spouses.